2017
DOI: 10.1186/s12864-017-4195-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of 39 Akkermansia muciniphila isolates reveals its population structure, genomic and functional diverisity, and global distribution in mammalian gut microbiotas

Abstract: Background Akkermansia muciniphila is one of the most dominant bacteria that resides on the mucus layer of intestinal tract and plays key role in human health, however, little is known about its genomic content.ResultsHerein, we for the first time characterized the genomic architecture of A. muciniphila based on whole-genome sequencing, assembling, and annotating of 39 isolates derived from human and mouse feces. We revealed a flexible open pangenome of A. muciniphila currently consisting of 5644 unique protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(155 citation statements)
references
References 61 publications
8
143
2
2
Order By: Relevance
“…Hence, we focused our attention to the kinetic characterization of the A. muciniphila NagB homologue. It should be noted that the recent genome sequencing of 39 A. muciniphila isolates might result in the discovery of genes coding for a functional NagB homologue, especially because of the great differences found between strains in the amino sugar metabolism (Guo et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we focused our attention to the kinetic characterization of the A. muciniphila NagB homologue. It should be noted that the recent genome sequencing of 39 A. muciniphila isolates might result in the discovery of genes coding for a functional NagB homologue, especially because of the great differences found between strains in the amino sugar metabolism (Guo et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Guo et al . () reported a high genetic diversity of A. muciniphila by whole‐genome sequencing, with 5644 unique proteins assembling a flexible open pangenome. They further classified A. muciniphila into three species‐level phylogroups, which demonstrated different function features.…”
Section: Characteristics Of a Muciniphilamentioning
confidence: 99%
“…The genome of A. muciniphila strain MucT (=ATCC BAA-835T=CIP 107961T) involves one circular chromosome of 2.66 Mbp, which shared a limited number of genes (29%) with its closest relatives in the Verrucomicrobia phylum (van Passel et al, 2011). Recently, Guo et al (2017) reported a high genetic diversity of A. muciniphila by whole-genome sequencing, with 5644 unique proteins assembling a flexible open pangenome. They further classified A. muciniphila into three species-level phylogroups, which demonstrated different function features.…”
Section: Characteristics Of a Muciniphilamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a pangenomic study that included 33 new isolates from adults and 6 from laboratory mice provided insights into the population structure and evolutionary history of the Akkermansia lineage [14]. Specifically, this study revealed an open pangenome with at least three species-level phylogroups (AmI, AmII, and AmIII) that appear to be evolving independently.…”
Section: Introductionmentioning
confidence: 99%